2018
DOI: 10.3389/fneur.2018.00608
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Network Alteration and its Correlation With Structural Impairments in Patients With Depression in de novo and Drug-Naïve Parkinson's Disease

Abstract: Purpose: Depression is common in Parkinson's disease (PD) and is correlated with the severity of motor deficits and quality of life. The present study aimed to investigate alterations in the structural brain network related to depression in Parkinson's disease (d-PD) and their correlations with structural impairments of white matter (WM).Materials and Methods: Data were acquired from the Parkinson Progression Markers Initiative (PPMI) database. A total of 84 de novo and drug-naïve PD patients were screened and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 33 publications
3
41
0
Order By: Relevance
“…Foremost, these findings do not support the replication of a recent investigation by Huang et al (7) that compared DTI metrics of white matter integrity between PD groups with high and low symptoms of depression. However, the results of the current study did replicate the results of a more recent investigation of depression in PD, who likewise used PPMI data and comparable analysis techniques, and found no significant FA or MD white matter differences between a dPD and ndPD group (10). Overall, several studies using comparable methods to both the current study and Huang et al (7) have found mixed results (6, 9, 10).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Foremost, these findings do not support the replication of a recent investigation by Huang et al (7) that compared DTI metrics of white matter integrity between PD groups with high and low symptoms of depression. However, the results of the current study did replicate the results of a more recent investigation of depression in PD, who likewise used PPMI data and comparable analysis techniques, and found no significant FA or MD white matter differences between a dPD and ndPD group (10). Overall, several studies using comparable methods to both the current study and Huang et al (7) have found mixed results (6, 9, 10).…”
Section: Discussionsupporting
confidence: 83%
“…Even with these more sensitive approaches, there were no significant differences found between the extreme dPD and ndPD groups. Previous studies that had not found differences between these groups interpreted it as a result of using mild depression scores to distinguish the depressed group (10). However, the extreme group analysis in the current study suggests that there are not significant differences even when individuals with clinically significant levels of depression are compared to individuals with no depression.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Gou et al found no significant WM microstructural differences between depressed and non-depressed PD groups using TBSS (59), a finding that was replicated by Lacey et al using data from PPMI (53). However, connectivity analysis revealed significant network changes associated with PD patients with depression (59). Parkinson disease with apathy has also been associated with bilateral microstructural alterations in the medial corticostriatal limbic system; more specifically, decreased FA and increased MD were observed in the anterior striatum and pregenual anterior cingulate cortex, along with concomitant serotonergic dysfunction (62).…”
Section: Dti In Early-stage Pdmentioning
confidence: 96%